Failure of the Durom Metasul® Acetabular Component - Long, William T. (Springer-Verlag, 2009)
Large-diameter metal-on-metal articulations reportedly provide better stability and range of motion than smaller diameter bearings. We therefore asked whether a large-diameter (44- to 50-mm) metal-on-metal articulation (Durom®) would eliminate dislocation and provide similar functional scores and clinical and radiographic failure rates as those with 28-mm articulation. We prospectively followed 181 patients (207 hips) who had a large-diameter articulation implanted between May 2006 and November 2007. We compared these patients with a historical control of 54 patients who had a small-diameter (28-mm Metasul®) articulation. All patients had a Harris hip score and a self-assessment of outcome and radiographic followup. The minimum followup was 1 year (mean, 1.6 years; range, 1–2 years). During the followup period, we performed revisions on 29 patients (30 hips [15%]) with 21 of 29 (72%) having radiographic criteria of loosening. Thirteen retrieved cups and acetabular tissue were examined histologically. Twenty-eight of 151 unrevised patients had radiographic impending failure; 12 without revision had clinical failure. Eight patients (nine hips) had both clinical failure and impending radiographic failure. Cup inclination was 41.3° ± 5.4° and anteversion was 20.2° ± 7°. The revision rate and quality of clinical results were unacceptable as compared with our historical controls. We do not recommend use of the Durom® implant. Level of Evidence: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.